An experiment of water-responsive shape memory hybrid - Ng, Ban Hoe. (2013)
2 sets of 3 numbers of polymer sponge / polyethylene glycol hybrid (2cm by 2cm by 2cm) were fabricated with 25%, 50% and 75 % compression.